Resilience, Relationality, and Older People: The Importance of Intergenerationality. (December 2020) - Chappell, Anne; Welsh, Elaine
In this article, we examine the concept of resilience. Debates range from defining it as an individualised attribute to understanding it as a relational social process. Concerns about an ageing population alongside a growing interest in well-being have led to an increase in the use of the term 'resilience' in UK policy and political rhetoric. Developing strategies for 'bouncing back' from difficult circumstances has been at the heart of much discussion of resilience. Drawing on qualitative data from interviews and focus groups with older people in the UK, we explore their perspectives on resilience. We found that relationships, including intergenerational ones, are crucial to older people's understandings of resilience. Our data showed that narratives from the past were used to sustain resilience in the present and that negotiation and exchange between generations, as well as intergenerational connections in the community, fostered resilience among our participants. We found that relationality was at the heart of older people's perspectives on resilience and that the social process of resilience was acted out in their everyday interactions with others as well as through their memories of past interactions. This article argues that recognising the significance of these daily practices contributes to a more nuanced understanding of resilience.